NA TAJNYM FRONCIE. WZORZEC STRUKTURALNY I DZIAŁANIA SIATEK DYWERSYJNO-ROZPOZNAWCZYCH W NOWOCZESYM KONFLIKCIE ZBROJNYM. ANALIZA ASPEKTÓW W OPARCIU O ŹRÓDŁA OGÓLNODOSTĘPNE - WARCHAŁ Arnold; ŻUKOWSKI Przemysław (2016)
Topics considered in the area of special intelligence activities can be oriented towards the many levels of state’s security interests. When it comes to security strategy, the data acquired by an open source intelligence in addition to other sources converts into very important knowledge, sometimes vital and often instrumental for protection of state’s sovereignty. Information on subversive agenda of an aggressor is always hard to come by, but an open source analysis can be somewhat helpful in tracing possible goals, extent and capacity of foreign secret agenda to destabilize a country or a region. Recently we have an example of such activities, when we observe the Russian sponsored war effort in eastern Ukraine, and its Crimean peninsula annexation by subversive forces. Analyzing the information gathered in reference to Russian actions in Ukraine and its other neighbors, including especially Poland, we can observe specific pattern leading to control of important aspects of state’s security. Authors in the following article review available facts and data connected to intelligence subversion modes and activity patterns that may lead, as is exemplified by the case of Ukrainian conflict, to final gain in political or military goals.